Analisis Nilai Karakter Tanggung Jawab dalam Teks Cerita Buku Tematik Kelas IV SD/MI Tema 4 - Balqis, Tiara; Muktadir, Abdul; Tarmizi, Pebrian (JURIDIKDAS, 2025)
The purpose of this study was to describe the value of the character of responsibility in story texts in class IV thematic books, theme 4. The method used was qualitative research using a content analysis model. The instrument in this study is the table of indicators of the value of the character of responsibility. The data analysis technique was in the form of content analysis which consisted of four stages, namely design of investigation, collecting data, analyzing the data, and summarizing and integrating the findings. The validity of the data in this study uses semantic validity in the form of a lattice table of responsibility character values. The results of the study show that there are 12 story texts that contain the character values ​​of responsibility which are guided by 8 indicators, namely indicators of being serious in everything, doing your best, willing to sacrifice, disciplined, obedient to rules, trustworthy, honest in acting, and dare to take risks. In the 12 story texts in Theme 4 all of these indicators appear with different levels of occurrence of each indicator. The character indicators of responsibility that appear the most are willing to sacrifice.